Reconstructing the Concept of Entrepreneurial Culture in the Digital Age: A Cross-Cultural Theoretical Framework: Merekonstruksi Konsep Budaya Kewirausahaan di Era Digital: Kerangka Teoretis Lintas Budaya - Rofiqotur Riskiyah; Nur Syam (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
This study aims to reconstruct the concept of entrepreneurial culture within the context of the digital age through a cross-cultural theoretical approach. The global digitalization process has reshaped how entrepreneurs think, act, and interact, thereby requiring a renewed understanding of how cultural values, norms, and practices influence modern entrepreneurial behavior. The research employs a library research method by analyzing a wide range of up-to-date academic sources, including peer-reviewed international journals and relevant scholarly books. The literature analysis focuses on three key dimensions: (1) the evolution of the entrepreneurial culture concept, (2) the influence of digital transformation on cultural values and entrepreneurial behavior, and (3) the development of a cross-cultural theoretical framework to understand entrepreneurship in the digital era. The findings reveal that entrepreneurial culture in the digital era is not solely derived from traditional values such as innovation, risk-taking, and achievement orientation but is also shaped by digital dimensions such as technological adaptability, network culture, and digital ethics. Consequently, the reconstruction of entrepreneurial culture must consider the interplay between local and global cultural values mediated by digital technology. This study contributes to the development of a more inclusive and context-sensitive theory of entrepreneurship and provides a conceptual foundation for policymakers, educators, and scholars in designing relevant entrepreneurial models for the era of global digital transformation.